Philosophical biography : some problems of conceptualization - Irina Polyakova (Conserveries Mémorielles)
This article considers the specificity of the genre of philosophical biography and brings to light its conceptual grounds. “Philosophical biography” is defined as an understanding of human life, which has received not only a literary but also a philosophical form of expression. It shows that philosophical biography has a variety of features, which limit the applications of chronology, rubrication and other principles of organizing in a linear manner the material of a biography. In this context such notions as “life-course”, “trajectory”, and “life-course trajectory” are analyzed; and the grounds of the unity of biographical content are revealed.This article claims that the unity of biographical content is determined by the author’s philosophical worldview. This does not mean turning biography into a kind of philosophical theory, but it means a conceptualization of life, in accordance with certain principles or ideas. Two main ideas for the ground of conceptualization of the biographed life are proposed. First, life as a drama, in which the contradictions of worldview are on the front plan. A philosopher’s life-course has its own specific character: a dramatic process of (self-) formation, (self-) knowledge, which is impossible to view in a single linear perspective as we are faced with the nonlinear nature of events (thoughts and feelings can take the place of events, if they are deeply experienced and felt by the personality) and with the nonlinear nature of memory, understood as a creative act. Second, the idea of plasticity of man, which can’t be schematized or lined up, but can be conveyed by means such as the plastic philosophical narrative.